UPAYA MEREDUKSI PROKRASTINASI AKADEMIK MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK REINFORCEMENT POSITIF PADA SISWA KELAS XB SMA NEGERI 7 SURAKARTA TAHUN PELAJARAN 2025/2026 - Rifqotul Muna Ngatiyatul Maula; Arif Sutikno; Pamungkas Darubigso (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Learning is a process that knows no age or time. Learning does not only take place in school, but can also occur in the environment and community. In Indonesia, learning can be divided into three categories: informal, formal, and non-formal. In the learning process, each individual has their own priorities and self-management skills, as well as time management. In formal education, students are expected to manage their priorities and time effectively for learning. Poor time management can lead to delays in completing assigned tasks at school. Procrastination, or the tendency to postpone or delay tasks, involves not completing assignments on time or frequently being late to class. The phenomenon observed in schools, as indicated by the results of the observation, shows that there are students who still engage in procrastination or delay in completing tasks, resulting in tasks not being submitted on time. This is evidenced by the fact that out of 221 respondents, 3.31% experienced academic procrastination. Based on the observations conducted by the researcher, the students at SMA Negeri 7 Surakarta are classified as intelligent but lack time management skills. Based on the results of group counseling using positive reinforcement techniques, it was found that students could reduce their academic procrastination levels using positive reinforcement techniques. The researcher conducted two cycles, with each cycle consisting of one meeting. The results of the service in cycle 1 showed an increase from 62% to 67%, falling into the “good” category. The results of the service in cycle 2 showed an increase of 9% from cycle 1, with the percentage rising from 67% to 76%, also falling into the “good” category. Based on the success index, if the percentage of all aspects achieved ≥ 75%, then there is no need for a third cycle. Thus, the group counseling service using positive reinforcement techniques conducted by the researcher on students in class XB of SMA Negeri 7 Surakarta in the 2024/2025 academic year was able to reduce academic procrastination.